IDENTIFIKASI KOMPONEN GOLONGAN SENYAWA KIMIA DAN FRAKSI DARI EKSTRAK ETANOL KULIT BATANG KAYU MANIS - Nindi Waang; I Gusti Made Ngurah Budiana (Media Sains, 2024)
A research has been conducted on the identification of chemical compound components and sunscreen activity test of fractions from ethanol extract of cinnamon (Cinnamomum burmanii).  This study aims to test the sunscreen activity of each fraction. Identification of secondary metabolite compounds was carried out by phytochemical test method, while the sunscreen activity test used visible ultra violet spectroscopy method. The results showed that the ethanol extract content of cinnamon bark was 25.6%. The ethanol extract is blackish red while the n-Hexan fraction is maroon red, the ethyl acetate fraction is light orange and the distilled water fraction is mustard yellow. The results of sunscreen activity testing showed the SPF values of the n-Hexan fraction, ethyl acetate fraction and distilled water fraction were 33.17, 36.20, 25.45, respectively. In accordance with FDA standards, each fraction is categorized as all including ultra protection.